2022
DOI: 10.1097/01.asw.0000833604.12023.71
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Vasopressor Dose and the Incidence of Pressure Injuries in Critically Ill Patients

Abstract: OBJECTIVE:To evaluate risk factors associated with vasopressor use and development of hospital-acquired pressure injuries (HAPIs). METHODS:The researchers conducted a retrospective chart review in a 12-bed medical ICU at a community hospital. A total of 123 patients who received a minimum of 24 hours of continuous vasopressor administration between January 2017 and January 2019 were included. The primary outcomes assessed were vasopressor dose and HAPI incidence, with a subgroup analysis based on type. Seconda… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…Vasopressors contain epinephrine, norepinephrine, post‐pituitary hormone and dopamine, etc., often used to improve mean arterial pressure by stimulating the constriction of peripheral blood vessels and strengthen tissue hypoperfusions and hypoxia of vital organs among critically ill patients 40 . This change has an adverse effect on the surrounding tissues due to less hemorheology in the surrounding tissue, significantly increasing the likelihood of stress injury 41 . Among adults treated in a medical‐surgical intensive care unit, the use of vasopressors was related to an increased risk of pressure injury, which was not explicitly evaluated on the Braden scale 42 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Vasopressors contain epinephrine, norepinephrine, post‐pituitary hormone and dopamine, etc., often used to improve mean arterial pressure by stimulating the constriction of peripheral blood vessels and strengthen tissue hypoperfusions and hypoxia of vital organs among critically ill patients 40 . This change has an adverse effect on the surrounding tissues due to less hemorheology in the surrounding tissue, significantly increasing the likelihood of stress injury 41 . Among adults treated in a medical‐surgical intensive care unit, the use of vasopressors was related to an increased risk of pressure injury, which was not explicitly evaluated on the Braden scale 42 .…”
Section: Discussionmentioning
confidence: 99%
“…40 This change has an adverse effect on the surrounding tissues due to less hemorheology in the surrounding tissue, significantly increasing the likelihood of stress injury. 41 Among adults treated in a medical-surgical intensive care unit, the use of vasopressors was related to an increased risk of pressure injury, which was not explicitly evaluated on the Braden scale. 42 The requirement for mechanical ventilation was found to be a risk factor for DRPIs.…”
Section: Risk Factors Of Drpis In Adult Icumentioning
confidence: 99%
“…Cox [62] highlighted a strong association between the use of vasopressors and the occurrence of PI, identifying vasopressors as a risk factor for PI in the general population. Furthermore, Holt et al [63] found that while the dose of vasopressor may not affect the incidence of HAPI, patients receiving high-dose vasopressor develop PI earlier than in low-dose cohorts.…”
Section: Treatment Factorsmentioning
confidence: 99%
“…PU are one of the common complications in patients in neurology ICU[ 10 , 11 ], and their incidence is still high around the world[ 12 , 13 ]. Due to the severity of their condition and long-term bed rest[ 14 ], ICU patients are susceptible to external factors[ 15 ], leading to ischemic necrosis of the skin and underlying tissues[ 16 ], thus forming PU[ 17 ]. The occurrence of PU not only brings pain and discomfort to patients, but may also cause infection, prolong hospitalization, and even threaten life[ 18 ].…”
Section: Introductionmentioning
confidence: 99%